Development in North East People's Republic of China: An analysis of enterprise performance 1995 - 2002 - Xiao Geng; John Weiss (Asian Development Bank Institute (ADBI), 2005)
Regional disparities within the People's Republic of China are now an important policy question. Recently the three provinces of the north-east region has been identified as priority areas for regional development, along with the Western part of the country. The north-east is the old industrial heartland of the country and its economy is based around heavy industry, mineral extraction and state owned enterprises. This paper uses a unique database on medium and large-scale enterprises establish how far enterprise performance in the north-east differs from the national average and the reasons for any such differences. It finds that even allowing for industrial structure and ownership, performance in the north-east is significantly below that in the rest of the country. This is attributed to aspects of the investment climate in the region.
Keywords: 330; Asia; the People's Republic of China; enterprises; productivity; profitability; regional development; Regionale Entwicklung; Unternehmensentwicklung; Produktivität; China (Nordost)